Impact of COVID-19 pandemic lockdown on post-harvest management of fruits and vegetables in three districts of Andhra Pradesh - G, Sravani; Supriya, Sai; R, Lazima; P, Alisha; M, Srijaya (Journal of Postharvest Technology, 2024)
The spread of COVID-19 pandemic has forced nations to remain in lockdown and stopped all essential activities all over the world. In these  circumstances, India is not only plagued by this pandemic, but the emergencies due to COVID-19 have adversely affected the supply chain, and trade of fruits and vegetables. In the present study, impact of COVID-19 pandemic lockdown on postharvest management of fruits and vegetables  was studied using a quantitative research design. A sample size of 120 fruit and vegetable farmers were selected from Andhra Pradesh, India.  The information was collected through telephonic interviews with the aid of a semi structured questionnaire. The collected data was statistically  analyzed using descriptive statistics and Chi- square (χ2) testing of hypotheses was used to find out the association between variables. Findings showed that there was a significant statistical association (p
Keywords: COVID-19 pandemic lockdown,; post-harvest losses; post-harvest management